A meta‐analysis of effects of physiological integration in clonal plants under homogeneous vs. heterogeneous environments. (17th December 2020) - Wang, Jianyong; Xu, Tongtong; Wang, Yue; Li, Guangyin; Abdullah, Iram; Zhong, Zhiwei; Liu, Jushan; Zhu, Wanyue; Wang, Ling; Wang, Deli; Yu, Fei‐Hai
Abstract: Clonal plants play key roles in maintaining community productivity and stability in many ecosystems. Connected individuals (ramets) of clonal plants can translocate and share, for example, photosynthates, water and nutrients, and such physiological integration may affect performance of clonal plants both in heterogeneous and homogeneous environments. However, we still lack a general understanding of whether or how physiological integration in clonal plants differs across homogeneous versus heterogeneous environments. We compiled data from 198 peer‐reviewed scientific studies conducted in 19 countries with 108 clonal plant species from 35 families, and carried out a meta‐analysis of effects of physiological integration on 16 traits related to plant growth, morphology, physiology or allocation. Our analyses evaluated these relationships in (A) heterogeneous environments where at least one resource essential for plant growth (e.g. light, soil water and mineral nutrients) or non‐resource factor (e.g. grazing, trampling and burial) is spatially non‐uniformly distributed and (B) homogeneous environments where all these factors are spatially uniformly distributed. Physiological integration increased growth of whole clones in both homogeneous and heterogeneous environments due to its highly significant contribution to growth of recipient ramets. Integration did not affect growth of donor ramets in heterogeneous environments, but decreased it in homogeneous environments. Integration affected physiological traits of donor ramets in neither homogeneous nor heterogeneous environments. It did not affect any physiological traits of recipient ramets in homogeneous environments, but increased most of them in heterogeneous environments. For donor ramets, integration increased height by 53% and internode length by 37% in heterogeneous environments, but had no effect in homogeneous environments. For recipient ramets, integration increased height by 73% in homogeneous environments and by 115% in heterogeneous environments, and increased internode length by 35% only under heterogeneous environments. In heterogeneous environments, integration increased biomass allocation to roots of donor ramets under high water/nutrient conditions and decreased it under high light. Physiological integration plays a strong role in clonal plant physiology, morphology and growth, especially for recipient ramets in heterogeneous environments. Therefore, physiological integration may have contributed to the widespread of clonal plants in nature and their dominance in many ecosystems. It may also play important roles in invasion success of alien clonal plants and in maintaining functions and stability of ecosystems where clonal plants are abundant. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.